2019
DOI: 10.15226/2475-4714/4/1/00141
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization and pharmacological evaluation of marine polyphenols from the brown algae Padina pavonica

Abstract: Background and Aim: Natural products continue to be a primary resource in biomedicine and biotechnology. The marine environment is highly reserve for novel pharmaceutical and medical compounds. The aim of this work was to identify bioactive components from the brown seaweed Padina pavonica with specific pharmacological potential. Methods: In the present study, we investigated the efficacy of polyphenol fraction from Padina pavonica for in vivo anti-inflammatory activity using the carrageen an-induced paw edem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These antioxidant molecules are created in their body tissues in response to the harsh environment in which they inhabit [60]. Alshaikheid et al [20] investigated the efficiency or efficacy of the polyphenol fraction of P. pavonica for in vitro antioxidant activity using DPPH radical scavenging assay method. These findings indicated that the polyphenol fraction of P. pavonica is a promising bio source of compounds with antioxidant potential [12].…”
Section: 2quantitative Analysis Of Phytochemical Substances and Antio...mentioning
confidence: 99%
See 1 more Smart Citation
“…These antioxidant molecules are created in their body tissues in response to the harsh environment in which they inhabit [60]. Alshaikheid et al [20] investigated the efficiency or efficacy of the polyphenol fraction of P. pavonica for in vitro antioxidant activity using DPPH radical scavenging assay method. These findings indicated that the polyphenol fraction of P. pavonica is a promising bio source of compounds with antioxidant potential [12].…”
Section: 2quantitative Analysis Of Phytochemical Substances and Antio...mentioning
confidence: 99%
“…It is a source of bioactive metabolites that are not found in other species and is used in the pharmaceutical industry. These antioxidant molecules are created in the body's tissues in response to the harsh environment in which they live [20]. Antibacterial chemicals produced by macro algae of Egyptian Journal of Chemistry http://ejchem.journals.ekb.eg/ 2025 the P. Pavonica are useful in inhibiting the growth of many infections in humans and other animals [21].…”
Section: Introductionmentioning
confidence: 99%